Analisis Resiliensi Makro pada Perbankan Syariah dalam Pembiayaan Infrastruktur Publik - Nissa Arrasyidi; Sulastri Sulastri; Amri Fatehuddin Siddiq; M Nurhaikal Sam; Rudy Heryana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the resilience of Indonesian Islamic banking in financing public infrastructure amidst macroeconomic fluctuations from 2021 to 2025, evaluating its alignment with Maqashid Syariah principles. Amidst global financial instability and economic uncertainties, the research addresses a significant gap by empirically examining Islamic finance's role in infrastructure development. Utilizing descriptive qualitative methodology and a case study approach focused on syndicated financing and the Musyarakah Mutanaqishah (MMq) contract for public utility sectors (electricity, gas, and water), the study analyzes secondary data from OJK and corporate annual reports. Findings reveal a robust and consistent growth in Islamic bank financing for the utilities sector, demonstrating significant resilience. The successful implementation of syndicated financing in renewable energy and water supply projects, alongside the effective use of MMq in mitigating macroeconomic risks and ensuring asset ownership transparency, are highlighted. Substantively, this financing framework aligns with Maqashid Syariah, promoting the protection of wealth (hifdz al-mal) from usury, life (hifdz an-nafs) through enhanced public utilities, and future generations (hifdz an-nasl) by avoiding speculative debt.